Comparative efficacy of non-pharmacological interventions for Parkinson’s disease with constipation: a systematic review and network meta-analysis - Peiying Zhang; Xiaojuan Su; Xuan Han; Dingmeng Zhao; Jinyan Wang; Yanyi Yang; Hejiang Ye (Frontiers in Neurology)
BackgroundThis network meta-analysis aims to evaluate the comparative efficacy of non-pharmacological interventions on Parkinson’s disease (PD) with constipation.MethodsA comprehensive search was conducted in seven major databases (CINAHL, the Cochrane Central Register of Controlled Trials [CENTRAL], Embase, PubMed, Web of Science, Chinese National Knowledge Infrastructure [CNKI], and Wanfang) up to August 2024. Eligible randomized controlled trials (RCTs) that evaluated non-pharmacological interventions for PD with constipation were included. Methodological quality was assessed using the Cochrane Risk of Bias tool, and a frequentist network meta-analysis (NMA) was performed using STATA 18 to estimate relative treatment effects.ResultsFrom 2084 initially identified records, 12 RCTs (n = 881 patients) met inclusion criteria. The four interventions evaluated included complementary and alternative medicine (CAM), evidence-based nursing (EBN), physical agents (PAs), and traditional Chinese medicine (TCM). Direct comparisons revealed significantly superior efficacy for both EBN and PAs compared to control conditions (p < 0.05). The NMA demonstrated consistent superiority of PAs and EBN over passive control, placebo, and sham interventions (all p < 0.05), with the following efficacy hierarchy: PAs (most effective) > EBN > CAM > TCM (least effective).ConclusionOur findings suggest that non-pharmacological approaches, particularly PA-based interventions, may offer clinically meaningful benefits for constipation management in PD. Nevertheless, the relatively small number of available studies and methodological limitations in several trials necessitate cautious interpretation. Further rigorously designed RCTs are warranted to confirm these preliminary observations and establish optimal treatment protocols.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42024565248.